NILAI-NILAI MULTIKULTURALISME DALAM AL-QUR’AN & URGENSI SIKAP KEBERAGAMAAN MULTIKULTURALIS UNTUK MASYARAKAT INDONESIA - Masthuriyah Sa’dan (Lembaga penelitian dan pengabdian kepada masyrakat, 2015)
Indonesian muslim society was judgment that multiculturalism is a method for faith shallow muslim in be religious and go in the pluralism until religion’s as it should be nothing differen or equal. Whereas Indonesian people have “bhinneka Tunggal Ika” symbol but the reality it is nonsense. Muslim people always make us of teks interpretasion (Qur’an) for ligitimision group need, class, or religios need. Because of that, investigate interpretasion teks Qur’an by fenomenology approach for teks Qur’an be correlation for multiculturalism is important for research